2020
DOI: 10.3390/microorganisms8081192
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lactic Acid-Fermented Tomato Products

Abstract: Background: lactic acid fermentation was recently proposed to produce fruit and vegetable beverages with high nutritional value. In this study, a wide screening of strains and fermentation parameters was carried out to develop fermented tomato-based drinks containing viable cells and potentially bioactive metabolites. Methods: six different products (three extracts, two tomato juices and one tomato puree) were used as substrate for fermentation. After preliminary testing, eight fermentation conditions for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…In general, the changes in polyphenols that occur after fermentation can also promote improvements in functional activity. Previous studies have reported that the antioxidant activities of tomato ( Ricci et al, 2020 ), cabbage ( Satora et al, 2021 ), and apple juices ( Wu et al, 2020 ) were enhanced by LAB strains, such as Lacticaseibacillus casei , Pediococcus acidilactici , and Lactobacillus helveticus .…”
Section: Introductionmentioning
confidence: 99%
“…In general, the changes in polyphenols that occur after fermentation can also promote improvements in functional activity. Previous studies have reported that the antioxidant activities of tomato ( Ricci et al, 2020 ), cabbage ( Satora et al, 2021 ), and apple juices ( Wu et al, 2020 ) were enhanced by LAB strains, such as Lacticaseibacillus casei , Pediococcus acidilactici , and Lactobacillus helveticus .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various studies have been dedicated to the lactic acid fermentation of different substrates [79,80] using Lacticaseibacillus rhamnosus for the evaluation of the aromatic component which undergoes modifications during the process. Fermentation can be used to increase aromatic notes [81] or to reduce off-flavor components in the products [82]. Changes to the aromatic profile derive from the metabolism of bacteria which, depending on the various nutritional compounds available, produce different metabolites.…”
Section: Lactic Acid Bacteria: Biological Resources For Volatile Compmentioning
confidence: 99%
“…Determination of free radical-scavenging activity (FRSA) through DPPH• inhibition represents the most common method for determination of antioxidant activity in plant materials, including pomegranate [30]. It is also a convenient method for evaluation of the antioxidant activity of fermented products [31][32][33]. Due to the fact that many studies on pomegranate and other fruit juices have utilized this method, for such measurements [15,[34][35][36] or even in combination with other methods [37,38], it was adopted in the present work in order to facilitate comparisons with relevant literature information.…”
Section: Antioxidant Activity and Phenolic Compoundsmentioning
confidence: 99%